A novel mutation in ATM gene in a Saudi female with ataxia telangiectasia. (9th January 2021) - Algahtani, Hussein; Shirah, Bader; Algahtani, Raghad; Al-Qahtani, Mohammad H.; Abdulkareem, Angham Abdulrahman; Naseer, Muhammad Imran
Abstract: Ataxia telangiectasia is a hereditary multisystem disorder with a wide range of symptoms and signs. It is inherited in an autosomal recessive manner due to a mutation in the ataxia telangiectasia mutated ( ATM ) gene, which encodes a protein kinase with a domain related to a phosphatidylinositol 3-kinase (PI-3 kinase) proteins that respond to DNA damage by phosphorylating key substrates involved in DNA repair and/or cell cycle control. The characteristics of the disease include progressive cerebellar ataxia beginning between ages one and four years, oculomotor apraxia, choreoathetosis, telangiectasias of the conjunctiva, immunodeficiency with frequent infections, and an increased risk for malignancy. In this article, we report a novel homozygous missense variant c.1516G > T, p.(Gly506Cys) in the ATM gene causing ataxia telangiectasia in a Saudi female. This variant led to the development of a later onset disease (at the age of 14 years) and the classical neurodegenerative process both clinically and on imaging. However, no immune system dysfunction or endocrine abnormalities were present. This is the second novel mutation in this gene so far reported from Saudi Arabia. The novel mutation described in the present study widened the genetic spectrum of ATM -associated diseases, which will benefit studies addressing this disease in the future.